MINISTÉRIO PASTORAL METODISTA NO DISTRITO ECLESIÁSTICO DE PIRACICABA: UM ESTUDO DE CASO SOBRE A PRÁXIS DE SOLIDARIEDADE NO CONTEXTO DA GLOBALIZAÇÃO - Oliveira, Márcio Divino de (2007)
The advance of economic globalization, responsible for some progress in humanity, but also for profound social problems, for example, the increase in the multitude of excluded and poverty stricken in the world is readily observable in contemporary settings. Together with this is the current emergence of market based religion, or, in other words, a religion that is private, hedonistic, non-historical, and without commitment to social dramas or values such as solidarity. This setting presents challenges to the pastoral praxis of the church. In this sense, the current work, situated in the area of Religious Praxis and Society, has as its objective to analyze how the Methodist pastoral praxis of solidarity presents itself in these times of economic globalization. The research emphasizes that the Methodist church is guided by an Episcopal government, and is organized geographically and politically into eight (08) Ecclesiastical regions. Each Ecclesiastical region has internal subdivisions, called districts. Each local church, district, and region is linked in a connectional form within the Methodist system. Since a study of Methodist pastoral praxis at a national level is impossible, the present research seeks to explore the praxis of solidarity of Methodist pastors in the Ecclesiastical District of Piracicaba. As such, this work utilizes the method of critical historical analysis. The relevance of this research is in demonstrating the interaction between a sector of Brazilian Protestantism and economic globalization, making possible the evaluation of certain changes and/or transformations that this exchange provokes and its implications for the expression of Methodist pastoral praxis solidarity in the contemporary setting.